Verbal Specifics of Urban Space as Part of a National Communication Culture - Лихачева, Алла Борисовна (Slavistica Vilnensis, 2017)
In works dedicated to the Russian communication culture, the theme of correlation between the linguistic aspects of urban space and the features of Russian communication remains untouched. At the same time, it can be assumed that in the overall context of national communication culture, proper attention should be paid to the names of urban objects, as they are like an identifying mark of the city, transmitting important sociocultural information about it and objectifying the communication tonality and style between the city and the urban community.The paper discusses linguistic means by which communication is formed in the urban space, in line with the principles of Russian communication culture, implying closeness of the interacting parties and their awareness of the rules of such communication. In addition, the names of urban objects produce the effect of being part of a national linguacultural habitat.
Keywords: Russian communication culture; urban nominations; Russian communication style; national linguacultural habitat